Multilevel model in the identification of behavioral and structural risk factors for HIV: integrative review - Juliana Kelly Batista da Silva; Jamira Martins dos Santos; William Caracas Moreira; Renata Olívia Gadelha Romero; Oriana Deyze Correia Paiva Leadebal; Jordana de Almeida Nogueira (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to investigate studies that adopted the multilevel analysis model to identify behavioral and structural risk factors associated with HIV infection. Methods: an integrative review of the literature with studies available in full, obtained from EMBASE, CINAHL, Pubmed, and Scopus, whose selected descriptors were the indexed terms: "HIV", "multilevel analysis" and "behavior". Results: the search resulted in 236 studies. Out of these, ten studies comprised the sample. Economic disadvantage, neighborhood characteristics, housing instability, incarceration, transactional sex, multiple partners, substance abuse, and age at first intercourse were classified as structural and behavioral risk factors for HIV. Reduced socioeconomic disadvantage, provision of housing stability, and condom use were associated with protective factors for HIV exposure. Conclusions: by applying the multilevel model in risk factor research studies, it was possible to identify the structural and behavioral elements of HIV risk.